1997
DOI: 10.1136/gut.41.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure and body composition in children with Crohn’s disease: effect of enteral nutrition and treatment with prednisolone

Abstract: Background-Malnutrition and growth retardation are common complications of Crohn's disease in children. The contribution of resting energy expenditure (REE) to malnutrition is unclear. Aims-To characterise the REE and body composition in children with Crohn's disease and compare them with normal controls and patients with anorexia nervosa; to compare the eVects of prednisolone and enteral nutrition on energy expenditure and body composition. Subjects-Twenty four children with Crohn's disease, 19 malnourished f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
2
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 33 publications
8
96
2
3
Order By: Relevance
“…In these patients malnutrition is often reported, especially in CD patients with active disease (Harries & Heatley, 1983;Fernandez-Banares et al, 1989Cristie & Hill, 1990;Janczewska et al, 1991;Stokes, 1992;Kuroki et al, 1993, Royall et al, 1995Teahon et al, 1995;Zurita et al, 1995;Ascue et al, 1997;Capristo et al, 1998). In a recent study, we found several nutritional and functional de®ciencies in patients with longstanding CD, currently in remission (Geerling et al, 1998a, b).…”
Section: Introductionmentioning
confidence: 85%
“…In these patients malnutrition is often reported, especially in CD patients with active disease (Harries & Heatley, 1983;Fernandez-Banares et al, 1989Cristie & Hill, 1990;Janczewska et al, 1991;Stokes, 1992;Kuroki et al, 1993, Royall et al, 1995Teahon et al, 1995;Zurita et al, 1995;Ascue et al, 1997;Capristo et al, 1998). In a recent study, we found several nutritional and functional de®ciencies in patients with longstanding CD, currently in remission (Geerling et al, 1998a, b).…”
Section: Introductionmentioning
confidence: 85%
“…As shown by several authors [23,24,25], children with active CD have significantly reduced energy intake, which normalizes during remission. Literature is controversial regarding the effect of IBD on resting energy expenditure (REE) [26,27,28,29], probably due to the way results are expressed. Even though REE tends to decrease in anorexia as a sparing mechanism, some authors found an increase in REE, presumably due to inflammation and body composition changes in IBD patients [26,27,28,29].…”
Section: Growth Failure In Pediatric Ibdmentioning
confidence: 99%
“…In addition, the increased oxidation of leucine observed in their study suggested significant essential amino acid loss, with protein loss observed even in the postabsorptive state. However, enteral nutrition resulted in greater increases in fat free mass than corticosteroid therapy in children with active Crohn disease (22).…”
Section: Discussionmentioning
confidence: 99%